Crystalline and Amorphous Preparation of Aluminum Hydroxide Nanoparticles Enhances Protective Antigen Domain 4 Specific Immunogenicity and Provides Protection Against Anthrax - Gogoi H (Dove Medical Press, 2020)
Himanshu Gogoi, 1 Rajesh Mani, 1 Soumya Aggarwal, 2 Anshu Malik, 1 Manoj Munde, 2 Rakesh Bhatnagar 1, 3 1Laboratory of Genetic Engineering and Molecular Biology, School of Biotechnology, Jawaharlal Nehru University, New Delhi, India; 2School of Physical Sciences, Jawaharlal Nehru University, New Delhi, India; 3Banaras Hindu University, Varanasi, Uttar Pradesh, IndiaCorrespondence: Rakesh BhatnagarBanaras Hindu University, Room No. 102, New Delhi, IndiaEmail rakeshbhatnagar@jnu.ac.inIntroduction: Aluminum salts, although they have been used as adjuvants in many vaccine formulations since 1926, exclusively induce a Th2-biased immune response, thereby limiting their use against intracellular pathogens like Mycobacterium tuberculosis.Methods and Results: Herein, we synthesized amorphous and crystalline forms of aluminum hydroxide nanoparticles (AH nps) of 150– 200 nm size range. Using Bacillus anthracis protective antigen domain 4 (D4) as a model antigen, we demonstrated that both amorphous and crystalline forms of AH nps displayed enhanced antigen D4 uptake by THP1 cells as compared to commercial adjuvant aluminum hydroxide gel (AH gel). In a mouse model, both amorphous and crystalline AH nps triggered an enhanced D4-specific Th2- and Th1-type immune response and conferred superior protection against anthrax spore challenge as compared to AH gel. Physicochemical characterization of crystalline and amorphous AH nps revealed stronger antigen D4 binding and release than AH gel.Conclusion: These results demonstrate that size and crystallinity of AH nps play important roles in mediating enhanced antigen presenting cells (APCs) activation and potentiating a strong antigen-specific immune response, and are critical parameters for the rational design of alum-based Th1-type adjuvant to induce a more balanced antigen-specific immune response.Keywords: aluminum hydroxide gel, crystalline nanoparticles, NLRP3 inflammasome, Th1/Th2 immune response, amorphous nanoparticles